2021
DOI: 10.1038/s41586-020-03114-6
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy renders cancer cells vulnerable to mitotic checkpoint inhibition

Abstract: U. (2021).Aneuploidy renders cancer cells vulnerable to mitotic checkpoint inhibition. Nature, 590(7846).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
187
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(231 citation statements)
references
References 73 publications
17
187
0
Order By: Relevance
“…To test this hypothesis, we interrogated the association between NF‐κB activation and the degree of aneuploidy in full‐blown tumors using the cancer cell line encyclopedia [CCLE; (Barretina et al , 2012 ; Ghandi et al , 2019 )]. The degree of aneuploidy was scored in almost 1,000 cell lines in the CCLE as recently described (Cohen‐Sharir et al , 2021 ). We then created two groups of cell lines, a highly aneuploid and a near‐euploid group, defined as the top and bottom quartiles of the number of arm‐level chromosome gains and losses, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we interrogated the association between NF‐κB activation and the degree of aneuploidy in full‐blown tumors using the cancer cell line encyclopedia [CCLE; (Barretina et al , 2012 ; Ghandi et al , 2019 )]. The degree of aneuploidy was scored in almost 1,000 cell lines in the CCLE as recently described (Cohen‐Sharir et al , 2021 ). We then created two groups of cell lines, a highly aneuploid and a near‐euploid group, defined as the top and bottom quartiles of the number of arm‐level chromosome gains and losses, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We examined data from a collection of 367 human cancer cell lines from the Cancer Cell Line Encyclopedia (CCLE) with matched DNA copy number, RNA expression and protein expression data [49][50][51][52][53][54] (Supplementary Data 1). We used a recently-described dataset in which each chromosome arm in a cell line was classified as "lost", "gained", or "neutral", relative to that cancer cell line's basal ploidy 55 . We calculated mean RNA and protein expression differences along each chromosome arm between cell lines with neutral ploidy for that arm and cell lines in which that arm was either gained or lost (Supplementary Data 2).…”
Section: Mean Protein Expression Increases Upon Chromosome Gain and Decreases Upon Chromosome Lossmentioning
confidence: 99%
“…Two recent studies also identified the KIF18A vulnerability, using orthogonal approaches to identify tumors with ploidy abnormalities and their genetic dependencies based on complementary loss-of-function screens. Cohen-Sharir et al 14 leveraged publicly available genomic data from the Cancer Cell Line Encyclopedia (CCLE) to quantify aneuploidy in cancer cells based on copy number changes affecting whole chromosome arms. Core SAC genes BUB1B and MAD2 ranked as the most preferential individual genetic dependencies in aneuploid cell lines, while the SAC as a whole scored among the most preferentially essential pathways.…”
mentioning
confidence: 99%